Development of cutting tool through superplastic deformation methods on boronized duplex stainless steel / Mazlan Shah - Mazlan, Shah (2013)
In this study, focus was set upon developing new method to produce cutting tool through the employment of superplastic boronizing and duplex stainless steel, within which formation of the cutting tool from boronized duplex stainless steel subjected to superplastic deformation was tested against the determining parameters, strain and strain rate. As received DSS specimen was thermo-mechanically treated by heating up to 1537K, holding for one hour, followed by water quenching and then cold rolled to a plate through a reduction area of 75%. Prior to superplastic forming, treated DSS was boronized at 1223K for 6 hours, thereafter producing average surface hardness of 2247 HV and layer thickness of 46.3 μm. Then, the specimen was superplastically deformed into designated cutting tool at 1223K with the strain rate of 1x10-4 and 9x10-5 s-1. Result showed that the flow stress of the deformed specimen was higher at the faster strain rate. At slower strain rate and low strain (0.4), no flaws were observed at the surface of the deformed specimen. However, at faster strain rate and higher strain (0.8 and 1.0) flaws that lead to surface disintegration were observed. It is very crucial to control these parameter (strain rate and strain) to avoid any surface flaw (disintegrity) to the specimen.